Rural Tourism Sustainable Management and Destination Marketing Efforts: Key Factors from Communities’ Perspective - Chee-Hua, Chin; Lo, May-Chiun; Ramayah, T. (Canadian Center of Science and Education, 2016)
Rural tourism is seen as a potential sector in promoting country to the world and at the same time generates incomes to local communities. However, due to the lucrative economic benefits, tourism destination’s sustainability and quality of services is often being ignored. Thus, this study highlights the importance of sustainable management and destination marketing efforts in rural tourism destinations with identified significant contributively factors from local communities’ perspective. A total of 168 respondents comprising of local communities from Kampung Telaga Air and Kampung Semadang, Kuching, Sarawak took part voluntarily in this study. To assess the developed model, SmartPLS 2.0 (M3) is applied based on path modelling and bootstrapping. Interestingly, the findings revealed that local communities believed factors like climate change, carrying capacity of a destination, and environmental education are significantly affect both tourism destination sustainable management and destination marketing efforts. Furthermore, community support is also found to be important too for tourism destination marketing efforts. Surprisingly, community support was found no relations with destination sustainable management from local communities’ point of view. This study further discussed on the implications of the findings, limitations, and direction for future research.